Temporal profile of lymphocyte counts and relationship with infections with fingolimod therapy. (April 2014) - Francis, G; Kappos, L; O'Connor, P; Collins, W; Tang, D; Mercier, F; Cohen, JA
Background: Reduction in peripheral blood lymphocytes is an expected pharmacodynamic outcome of fingolimod therapy. Objective: The objective of this article is to evaluate lymphocyte dynamics during and after fingolimod therapy and assess the relationship between lymphocyte counts and infections. Methods: Lymphocyte counts and their relationship with infections were evaluated in three multiple sclerosis (MS) populations: (Group A) FREEDOMS phase 3 core study group ( n = 1272); (Group B) All Studies group (one phase 2 and two phase 3 studies, plus their extensions; n = 2315); and (Group C) Follow-up group (after fingolimod discontinuation; n = 538). Results: Administration of fingolimod 0.5 mg led to reductions in lymphocyte counts to a steady-state of 24%–30% of baseline values within two weeks, which remained stable while on therapy. Following fingolimod discontinuation, average counts exceeded the lower limit of normal range within six to eight weeks, and were 80% of baseline values by three months. In Group A, infection rates per patient-year were 1.4 with placebo and 1.0 in fingolimod-treated patients who had the lowest lymphocyte counts (< 0.2 × 10 9 /l). No evidence was seen for an increase in serious or opportunistic infections. Conclusions: Fingolimod induces a rapid and reversible reduction in lymphocyte counts without an increase in infections relative to placebo. Because fingolimod reduces blood lymphocyte counts via redistribution in secondary lymphoid organs, peripheral blood lymphocyte counts cannot be utilized to evaluate the lymphocyte subset status of a patient.